Engaging your audience: using altmetrics to drive faculty outreach and raise the profile of expertise within an institution - Lambe, Lucy; Bucknell, Terry (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. Today’s researchers exist in a very connected world, in which scholarly knowledge is rapidly published, disseminated and shared online amongst a global audience. They are communicating their research between each other and with the wider world, aiming to make an impact on society. Gathering evidence of this activity can provide powerful and data-driven insights into the reach and influence of specific content, which can then be utilised to help develop an individual’s professional reputation and build future strategy. Online tools such as Altmetric can collect and analyse this data, and present it in a way that makes sense to researchers and university administrators. In this session we’ll explore why the London School of Economics is supporting altmetrics as a priority for identifying impact. We will discuss the tools and workflows that make this effective and engaging for researchers, and enable a broad view of departments and the institution as a whole. We’ll have examples of how the information that the Altmetric Explorer collates can then be interpreted and incorporated into reporting, statements of impact and supplement the traditional metrics academics already use. You will also find out how LSE have used altmetric data to generate engagement between the library, research office and faculty. Altmetrics can provide the data for a story of how research is creating impact. At LSE the library is working with the research office, department heads and individual researchers to identify and interpret this data, combined with citation metrics to create an overall picture of the activities of the School and staff. In particular, we’ll focus on what benefits this brings both the institution as a whole, and the individual researcher. Attendees will leave the session with some practical tips for how they can begin to get familiar with such data themselves, and some ideas to help them consider how they might integrate similar practices within their own organisation.